Wykształcenie ziemiańskie i jego wpływ na wychowanie dzieci na przykładzie rodu Ostrowskich Korabitów - Studnicka-Mariańczyk, Karolina (Biuletyn Historii Wychowania, 2013)
The article presents the subsequent stages of Aleksander Ostrowski’s education; it shows his successes at school, and also points at the direct link between the economic achievements of the Ostrowskis’ domain and the level of the owners’ education. The general and professional knowledge acquired at school and the level of culture and civil awareness provided resulted in the formation of high educational ambitions also in the next generation: the atmosphere of the family home and the pedagogical attitude of Aleksander and Helena Ostrowski influenced the fact that their children were also well educated; therefore, they could continue the family traditions, develop their farm, and participate in political life. The example of the Ostrowski family from Maluszyn can serve as an argument justifying the statement that a high level of education should be treated as a main factor in forming certain types of world views, social and political beliefs, and the level of interest and participation in culture. It should also be treated as a factor determining openness towards innovations and progress in both the organisation of social life and the economy.